The “I Designed It Myself” Effect in Mass Customization - Franke, Nikolaus; Schreier, Martin; Kaiser, Ulrike (Management Science, 2010)
Many companies offer websites that enable customers to design their own individual products, which the manufacturer can then produce to order. To date, the economic value of products self-designed using mass customization (MC) toolkits has been attributed to the two factors of preference fit achieved (which should be as high as possible) and design effort (which should be as low as possible). On the basis of literature on behavioral decision making, we suggest a third factor, namely the awareness of being the creator of the product design. In the course of five different studies, we provide experimental evidence that this “I designed it myself” effect creates economic value for the customer. Regardless of the two other factors, self-designed products generate a significantly higher willingness to pay. This effect is mediated by feelings of accomplishment and moderated by the outcome of the process as well as the individual's perceived contribution to the self-design process. These findings have important implications for MC companies: It is not enough merely to design MC toolkits in such a way that preference fit is maximized and design effort is minimized. To capture the full value of MC, toolkits should also elicit “I designed it myself” feelings.